A Method to Isolate CD34+ Mononuclear Cells from Canine Peripheral Blood. (22nd March 2019) - Kasimanickam, Vanmathy; Kasimanickam, Ramanathan
Abstract: Embryonic stem cells are pluripotent whereas adult stem cells are multipotent in nature. In recent years, evidence suggests that adult stem cells not only differentiate into specific cell lineages but also transdifferentiate into multiple cell lineages. Progenitor cells are found in adult bone marrow, blood, and other organs and differentiate into numerous cell lineages regardless of origin. Identifying a subset that can differentiate into mature endothelial cells is essential. This article describes peripheral blood collection in adult beagle dogs, isolation of peripheral blood mononuclear cells (PBMNCs) from the cell fraction, separation of a subset of CD34+ cells using immunomagnetic principles, characterization of PBMNCs and CD34+ cells using flow cytometry, and evaluation of gene expression of CD34, KDR, and CD133 in CD34+ fractions. Efficient methods of isolation of endothelial progenitor cells (EPCs) will promote the ex vivo expansion and transplantation of EPCs in ischemic injury to enable neovascularization. © 2019 by John Wiley & Sons, Inc.